Validation of a new procedure to determine plasma fatty acid concentration and isotopic enrichment - Patterson, Bruce W.; Zhao, Guohong; Elias, Nizar; Hachey, David L.; Klein, Samuel (Journal of lipid research, 1999)
Assessment of free fatty acid (FFA) concentration and isotopic enrichment is useful for studies of FFA kinetics in vivo. A new procedure to recover the major FFA from plasma for concentration and isotopic enrichment measurements is described and validated. The procedure involves extraction of plasma lipids with hexane, methylation with iodomethane (CH(3)I) to form fatty acid methyl esters (FAME), and subsequent purification of FAME by solid phase extraction (SPE) chromatography. The new method was compared with a traditional method using thin-layer chromatography (TLC) to recover plasma FFA, with subsequent methylation by BF(3)/methanol. The TLC method was found to be less reliable than the new CH(3)I method because of contamination with extraneous fatty acids, chemical fractionation of FFA species, and incomplete recovery of FFA associated with TLC. In contrast, the CH(3)I/SPE method was free of contamination, did not exhibit chemical fractionation, and had higher recovery. The iodomethane reaction was specific for free fatty acids; no FAME were formed when esterified fatty acids (triglycerides, cholesteryl esters, phospholipids) were subjected to the methylation reaction. We conclude that the CH(3)I/SPE method provides rapid and convenient recovery of plasma fatty acids for quantification or GC/MS analysis as methyl esters, and is not subject to the problems of contamination, reduced recovery, and chemical fractionation associated with recovery of FFA by TLC.